2020
DOI: 10.1002/adtp.202000083
|View full text |Cite
|
Sign up to set email alerts
|

pH‐Responsive STING‐Activating DNA Nanovaccines for Cancer Immunotherapy

Abstract: Cyclic dinucleotides (CDNs), such as c‐di‐GMP (CDG), are agonists for stimulator of interferon genes (STING) and are promising for cancer immunotherapy. Yet, the therapeutic efficacy of CDNs has been limited by poor delivery and biostability. Here, STING‐activating DNA nanovaccines (STING‐NVs) are developed, which biostabilize, deliver, and conditionally release CDG in the endosome of immune cells, elicit potent antitumor immune responses in murine and human immune cells, ameliorate immunosuppression in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…GSH is one of the most abundant reductive cellular metabolites, and it plays an important role maintaining the balance of the DEX-HAase nanoparticles 3-(bromomethyl)-4-methyl-2,5-furandione [24] PCL-Hyd-PEG vesicles Antigens HCP, adjuvants CpG ODN PCL-Hyd-PEG [25] Dendrigraft poly-l-lysines Zoledronic acid (ZA) 1,6-Bis(4-formylbenzoyloxy) hexane [26] RPTDH NPs R848 Poly-l-histidine (PHis) [27] Poly(ethylene glycol)-block-poly(diisopropanol amino ethyl methacrylate-co-hydroxyethyl methacrylate) (PDPA)-PPa Small interfering RNA (siRNA) OEI-C14 [28] PCPP hybrid micelles PD-L1-blockade siRNA, MTPP(PS) Amide bond [29] Nanogels PTX, IL-2 Chitosan polymers [30] CaCO 3 matrix CpG ODNs, IDOi, Ca 2+ CaCO 3 [31] H-MnO 2 nanoshells Ce6, DOX H-MnO 2 [32] Poly(ethylene glycol)-block-poly(D,L-lactide) (PEG-b-PLA) NPs CDNs cytosine (C) [33] pHLIP [34] Hollow silica nanoparticle Catalase, Ce6 [35] PDPM NPs OVA PDPA tertiary amino groups [36] PD-L1 binding peptide conjugate (DCS) NPs DOX, D-PPA Maleic acid amide bond [37] Sensitive cluster nanoparticles (SCNs) 1. 4-[2((1R,2R)-2-Hydroxycyclohexylamino)benzothiazol-6-yloxyl]-pyridine-2-carboxylic acid methylamide (BLZ-945), Pt-based prodrug Hydrophobic-hydrophilic transition [38] STING-NPs Cyclic guanosine monophosphate-adenosine monophosphate (cGAMP)…”
Section: High-level Gshmentioning
confidence: 99%
See 3 more Smart Citations
“…GSH is one of the most abundant reductive cellular metabolites, and it plays an important role maintaining the balance of the DEX-HAase nanoparticles 3-(bromomethyl)-4-methyl-2,5-furandione [24] PCL-Hyd-PEG vesicles Antigens HCP, adjuvants CpG ODN PCL-Hyd-PEG [25] Dendrigraft poly-l-lysines Zoledronic acid (ZA) 1,6-Bis(4-formylbenzoyloxy) hexane [26] RPTDH NPs R848 Poly-l-histidine (PHis) [27] Poly(ethylene glycol)-block-poly(diisopropanol amino ethyl methacrylate-co-hydroxyethyl methacrylate) (PDPA)-PPa Small interfering RNA (siRNA) OEI-C14 [28] PCPP hybrid micelles PD-L1-blockade siRNA, MTPP(PS) Amide bond [29] Nanogels PTX, IL-2 Chitosan polymers [30] CaCO 3 matrix CpG ODNs, IDOi, Ca 2+ CaCO 3 [31] H-MnO 2 nanoshells Ce6, DOX H-MnO 2 [32] Poly(ethylene glycol)-block-poly(D,L-lactide) (PEG-b-PLA) NPs CDNs cytosine (C) [33] pHLIP [34] Hollow silica nanoparticle Catalase, Ce6 [35] PDPM NPs OVA PDPA tertiary amino groups [36] PD-L1 binding peptide conjugate (DCS) NPs DOX, D-PPA Maleic acid amide bond [37] Sensitive cluster nanoparticles (SCNs) 1. 4-[2((1R,2R)-2-Hydroxycyclohexylamino)benzothiazol-6-yloxyl]-pyridine-2-carboxylic acid methylamide (BLZ-945), Pt-based prodrug Hydrophobic-hydrophilic transition [38] STING-NPs Cyclic guanosine monophosphate-adenosine monophosphate (cGAMP)…”
Section: High-level Gshmentioning
confidence: 99%
“…More importantly, STING-NVs can revert M2-like macrophages into antitumor M1-like macrophages, which effectively improved the effect of immunotherapy. [33] In addition, Ji et al reported an antibody or Fc fragment modified with polypeptides to target solid tumors (Figure 3f). Fc fragments or therapeutic monoclonal antibodies were conjugated with low pH-responsive polypeptides.…”
Section: Ph-responsive Nanoparticle For Immunotherapy Based On Other Typesmentioning
confidence: 99%
See 2 more Smart Citations
“…[2] Ligands alternative to CDNs and nanoparticles or hydrogels carrying CDNs are being actively pursued in order to overcome these limitations for the clinical applications. [7,8,[11][12][13][14][15][16][17][18][19] Despite these ongoing efforts, a facile therapeutic intervention that targets STING pathway is highly desired.…”
Section: Introductionmentioning
confidence: 99%